Corporate governance practices in microfinance institutions: Evidence from Uganda - Bob Ssekiziyivu; Rogers Mwesigwa; Juma Bananuka; Zainab Namusobya (Cogent Business & Management, 2018)
The purpose of this paper was to identify the corporate governance practices of Micro-finance institutions and to suggest strategies for improving corporate governance in Micro-finance institutions. This study was cross sectional and used a survey research design. Usable questionnaires were received from 179 respondents. Active Micro-finance institutions' members were the study's unit of inquiry. We analysed data with the help of statistical package for social scientists (SPSS). Findings suggest that Micro-finance institutions have boards though not effective, there are no fully constituted board committees, shareholders rights are sometimes not respected and accountability failures are common. Results further indicate the strategies for improving corporate governance such as having a board in place with financial expertise. Results are useful in policy formulation for example, Micro-finance institutions need to be regulated and a corporate governance code need to be put in place.
Keywords: 650